MARKETING STRATEGY TSANAWIYAH MADRASAH IN BANDAR LAMPUNG CITY - Fisman Bedi; Siti Patimah; Jamal Fakhri; Heni Noviarita; Koderi Koderi (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
This study focuses on analyzing how the marketing strategy of Madrasah Tsanawiyah in Bandar Lampung City uses a descriptive qualitative approach. The results of the study, Madrasah Tsanawiyah in determining the right product according to community demand will increase the number of student enthusiasts, the costs set must pay attention to purchasing power, affordability of costs, suitability of costs with product quality. In terms of the location of education, the availability of facilities and infrastructure that supports educational products offered with a sense of security and comfort. Promotions are carried out, more effectively by involving the user community as Customer Co-Creation by maximizing alumni and parents who have experienced educational products directly, on the other hand, the power of social media information flow is a separate choice in conducting promotions.